Cultivar-specific volatile profiles in Passiflora edulis determine thrips (Frankliniella intonsa) feeding preferences - Li, Wei; Ren, Ziwen; Wang, Tong; Wei, Xiaoxia; Wei, Hui; Tian, Houjun; Xu, Ruibin; Dong, Jiyang; Wu, Liangquan; Huang, Biao (Frontiers in Plant Science, 2025)
The issue that the attraction of leaf odors leading to thrips attacks affecting the yield and quality of Passion fruit (Passiflora edulis)—a high-value tropical crop in southern China has drawn widely attentions. This study aimed to comprehensively investigate the influences of special VOCs in susceptible and resistant passion fruit cultivars on feeding preferences of thrips. To explore the association between VOCs and insect behavior, the aromatic intensity of the selected cultivar leaves was determined. A total of 87 differential volatiles were identified from 423 VOCs using orthogonal partial least squares-discriminant analysis (OPLS-DA, P< 0.05, VIP > 1.0). Metabolic pathway analysis linked the differential volatiles to phenylpropanoid and α-linolenic acid metabolism. The key differential volatiles were fruity odor benzaldehyde and green odor (Z)-3-hexenol, which exhibited the highest rOAVs. Resistant cultivars accumulate high concentrations of benzaldehyde (OAV:191.49), which correlated with thrips attraction; while susceptible cultivars accumulated higher concentration of (Z)-3-Hexenol (OAV: 200.60), associated with repellency. Behavioral assays confirmed thrips preference for benzaldehyde (58% attraction) and aversion to (Z)-3-Hexenol (22% selection). These findings not only could advance our understanding of plant volatile-mediated insect behavior but also enable the development of lures for pest management, while providing a scientific basis for breeding pest-resistant cultivars.